Prarancangan Pabrik Cumene Dari Benzena Dan Propilen Menggunakan Proses Badger Dengan Desain Alat Utama Kolom Depropanizer (T-101) - Egi Lola Ariski (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Cumene is a compound that is very important for the development of the chemical industry, including its uses, among others, as a raw material for the manufacture of phenol, acetone, acetophenone, resins, solvents and terephthalic acid, while for the mechanical industry, cumene compounds are used for the manufacture of fuel additives with the aim of increasing aircraft piston engine capabilities. The cumene plant is designed using the Badger process with benzene and propylene as raw materials. The cumene plant with a capacity of 10,000 tons/year operates for 330 days/year and will be built in 2025 at the Dumai industrial area, Riau Province. The raw materials used are propylene and benzene using a new zeolite catalyst developed by (MCM-22), tested by Badger. The main tool designed is the Depropanizer (T-101) which functions to separate propane from its compounds. The depropanizer has a height of 10,657 m and a diameter of 3,278 m with a sieve tray distillation type and a torispherical head. The total investment capital for the cumene plant is Rp. 1,012,308,524,263 with a fixed cost of Rp. 151,846,278,639. The economic feasibility analysis of the plant shows that the plant is feasible to continue to the next stage of design, which can be seen from the analysis of the IRR value obtained by 22.83%, the ROI value of 58.21%, and the pay back period of 4.39 years. Keywords: benzene, propylene, cumene, depropanizer, badger process